Archaic thought and sophistry in herodotus’ histories 3.38.1 some remarks on the concept of νομος - Barrionuevo, Sergio Javier (2017)
The concepts of νόμος and φύσις were key to sophistical thinking. The sophistical opposition between the two concepts exerted a great influence in the fifth century BC. The objective of this contribution is to identify the presence of sophistical elements in Herodotus? Histories, taking a historical perspective. The approach will include an analysis of the notion of νόμος (?custom?). This examination is intended to demonstrate the thesis that Herodotus uses intellectual discussions from the fifth century BC but also transposes the concept of sophistry in order to restore an archaic conception of νόμος.